SIRT2, ERK and Nrf2 Mediate NAD+ Treatment-Induced Increase in the Antioxidant Capacity of PC12 Cells Under Basal Conditions - Zhang, Jie; Hong, Yunyi; Cao, Wei; Yin, Shankai; Shi, Haibo; Ying, Weihai (Frontiers in Molecular Neuroscience, 2019)
NAbstract NAD+ (oxidized form of nicotinamide adenine dinucleotide) administration is highly beneficial in numerous models of diseases and aging. It is becoming increasingly important to determine if NAD+ treatment may directly increase the antioxidant capacity of cells under basal conditions. In current study we tested our hypothesis that NAD+ can directly enhance the antioxidant capacity of cells under basal conditions by using PC12 cells as a cellular model. We found that NAD+ treatment can increase the GSH/GSSG ratios in the cells under basal conditions. NAD+ can also increase both the mRNA and protein level of -glutamylcysteine ligase – a key enzyme for glutathione synthesis, which appears to be mediated by the NAD+-induced increase in Nrf2 activity. These NAD+-induced changes can be prevented by both SIRT2 siRNA and the SIRT2 inhibitor AGK2. The NAD+-induced changes can also be blocked by the ERK signaling inhibitor U0126. Moreover, the NAD+-induced ERK activation can be blocked by both SIRT2 siRNA and AGK2. Collectively, our study has provided the first evidence that NAD+ can enhance directly the antioxidant capacity of the cells under basal conditions, which is mediated by SIRT2, ERK, and Nrf2. These findings have suggested not only the great nutritional potential of NAD+, but also a novel mechanism underlying the protective effects of the NAD+ administration in the disease models: The NAD+ administration can enhance the resistance of the normal cells to oxidative insults by increasing the antioxidant capacity of the cells.